2005
DOI: 10.1590/s0036-46652005000600004
|View full text |Cite
|
Sign up to set email alerts
|

Study of antiretroviral mutants in HIV patients with treatment failures and the effect of risk factors in the virological failures

Abstract: The most important factor related to treatment response in this study was adherence to treatment. Mutations in RT were related to the treatment failure while the ones found in PT were secondary mutations which have been previously described to influence the selection of primary resistance mutations in these regions. The study reveals the urgency to detect resistant mutations in VF to be considered by physicians for selection of treatment schedule, to analyze basal HIV patients for monitoring of the spread of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 26 publications
0
7
0
1
Order By: Relevance
“…Costa Rica has been able to provide better support for HIV patients undergoing treatment with a follow-up that showed a level of only 10% VF in the overall population treated. In an earlier study, we showed that all BS from patients who responded well to antiviral treatment had a viral load of < 10 4 copies/mL (12). In spite of that, we found a high viral variability in the VF patients, with low treatment adherence (Table 2).…”
Section: Discussionmentioning
confidence: 55%
See 4 more Smart Citations
“…Costa Rica has been able to provide better support for HIV patients undergoing treatment with a follow-up that showed a level of only 10% VF in the overall population treated. In an earlier study, we showed that all BS from patients who responded well to antiviral treatment had a viral load of < 10 4 copies/mL (12). In spite of that, we found a high viral variability in the VF patients, with low treatment adherence (Table 2).…”
Section: Discussionmentioning
confidence: 55%
“…In spite of that, we found a high viral variability in the VF patients, with low treatment adherence (Table 2). This variable, together with resistant mutants, was associated with VF in this early study (12). Variables such as sex, age, place of residence, risk group, occupation, and whether the persons were infected outside of Costa Rica were not found to correlate with HIV-1 intraor intersubtype.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations